Project iMARECULTURE: Advanced VR, immersive serious games and augmented reality as tools to raise awareness and access to European underwater cultural heritage - Skarlatos, Dimitrios; Agrafiotis, Panagiotis; Balogh, Tibor; Bruno, Fabio; Castro, Filipe; Davidde Petriaggi, Barbara; Demesticha, Stella; Doulamis, Anastasios D.; Drap, Pierre; Georgopoulos, Andreas; Kikillos, F.; Kyriakidis, Phaedon; et al. (My University, 2016)
The project iMARECULTURE is focusing in raising European identity awareness using maritime and underwater cultural interaction and exchange in Mediterranean Sea. Commercial ship routes joining Europe with other cultures are vivid examples of cultural interaction, while shipwrecks and submerged sites, unreachable to wide public are excellent samples that can benefit from immersive technologies, augmented and virtual reality. The projects aim to bring inherently unreachable underwater cultural heritage within digital reach of the wide public using virtual visits and immersive technologies. Apart from reusing existing 3D data of underwater shipwrecks and sites, with respect to ethics, rights and licensing, to provide a personalized dry visit to a museum visitor or augmented reality to the diver, it also emphasizes on developing pre- and after- encounter of the digital or physical museum visitor. The former one is implemented exploiting geospatial enabled technologies for developing a serious game of sailing over ancient Mediterranean and the latter for an underwater shipwreck excavation game. Both games are realized thought social media, in order to facilitate information exchange among users. The project supports dry visits providing immersive experience through VR Cave and 3D info kiosks on museums or through the web. Additionally, aims to significantly enhance the experience of the diver, visitor or scholar, using underwater augmented reality in a tablet and an underwater housing. The consortium is composed by universities and SMEs with experience in diverse underwater projects, existing digital libraries, and people many of which are divers themselves.
Keywords: Maritime; Underwater cultural interaction; Maritime cultural heritage; Virtual Museums